Chronic Urticaria Biomarkers IL-6, ESR and CRP in Correlation with Disease Severity and Patient Quality of Life—A Pilot Study - Matea Kuna; Mario Štefanović; Blaženka Ladika Davidović; Nikolina Mandušić; Ines Birkić Belanović; Liborija Lugović-Mihić (Biomedicines, 2023)
(1) Background: To assess the relationship between serum interleukin-6 (IL-6), erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) values and disease severity in patients with chronic spontaneous urticaria (CSU) and to examine which of these serum biomarkers better indicates disease severity. (2) Methods: Our pilot study included 20 patients with CSU who filled out questionnaires concerning disease severity and quality of life (the Urticaria Activity Score summed over 7 days [UAS7], the once-daily Urticaria Activity Score [UAS], the Urticaria Control Test [UCT], and the Dermatology Life Quality Index [DLQI]). Blood samples were taken to measure IL-6, ESR and CRP. (3) Results: ESR significantly correlated with the UAS7 (linear and moderate correlation; r = 0.496; p = 0.026), while CRP did not correlate with disease severity. IL-6 correlated with the once-daily UAS (r = 0.472; p = 0.036) and DLQI (r = 0.504; p = 0.023) (linear and moderate correlation) but not the UAS7 or UCT. (4) Conclusions: IL-6 was a better indicator of the once-daily UAS and DLQI, while ESR was a better indicator of the UAS7 (there was no correlation between IL-6, CRP and ESR parameters). Although our results are promising, this study should be conducted with a larger number of CSU patients.